Pengaruh Pengendalian Internal, Kompetensi dan Locus Of Control Pada Kecenderungan Kecurangan Akuntansi - Wirakusuma, I Gede Beni; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
This study aims to determine the effect of internal control, competence and locus of control on accounting fraud tendencies.This research was conducted in the Municipal Revenue Office with a survey method using a questionnaire. The number of samples analyzed was 80 respondents using a purposive sampling method. The data analysis technique in this study used multiple linear regression analysis.Based on the results of the analysis carried out, it can be concluded that the results of data analysis show that internal control and competence negatively affect the tendency of accounting fraud. Whereas locus of control has a positive effect on accounting fraud tendencies. Key word : Internal Control, Competence, Locus Of Control, Accounting Fraud Trends